FISCAL AND PSYCHOLOGICAL FACTORS OF TAX EVASION - Posadnieva, Oksana; Sidelnykova, Larysa (Socio-economic relations in the digital society, 2024)
The article is devoted to the study of behavioural factors that influence the decision-making of business entities and the population regarding tax evasion. The problem of tax evasion from the point of view of the influence of psychological characteristics of the individual and external economic factors on the deviant behaviour of taxpayers is considered. The influence of these factors on the volume of the shadow economy in the country is proven.The research allowed us to outline the main models that explain the reasons and motivations of taxpayers when they decide to violate tax legislation. It is emphasized that tax offences as a component of the shadow economy are present in many countries of the world. It is noted that the volume of violations increases with the onset of destructive events in the economy, such as economic and social crises and war. It is stressed that a significant role in the presence of deviant behaviour of taxpayers is played by their financial and legislative ignorance. The main elements of taxes that pose the greatest risks of tax evasion are identified.It has been found that the level of corruption in the country and the insufficient severity of possible punishment for tax crimes play a significant role in the decision of economic entities to evade taxation. An analysis of the corruption perception index in some countries has been made. It is proved that in less corrupt countries, tax collection is higher than in countries with high levels of corruption. It is emphasized that the lack of proper control by tax authorities leads to a larger scale of tax evasion, so it is necessary to conduct all legally established types of tax audits, despite the martial law in the country.
Keywords: behavioral factors; fiscal sociology; tax evasion; shadow economy; corruption perception index; tax control